2014
DOI: 10.1128/jvi.00239-14
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Suppressor Cylindromatosis (CYLD) Controls HIV Transcription in an NF-κB-Dependent Manner

Abstract: Characterizing the cellular factors that play a role in the HIV replication cycle is fundamental to fully understanding mechanisms of viral replication and pathogenesis. Whole-genome small interfering RNA (siRNA) screens have identified positive and negative regulators of HIV replication, providing starting points for investigating new cellular factors. We report here that silencing of the deubiquitinase cylindromatosis protein (CYLD), increases HIV infection by enhancing HIV long terminal repeat (LTR)-driven … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 79 publications
(115 reference statements)
0
20
0
Order By: Relevance
“…Results from this analysis led to the identification of 139 host factors that, when depleted, enhanced viral infection by 50% or more compared to the negative control with at least two independent siRNAs (Figure 1B; see Table S1 available online). Proteins involved in cell cycle regulation, ubiquitination, apoptosis, and DNA replication were found to be enriched in the set of 139 genes (Figure 1C), including CYLD, a gene we recently reported to regulate LTR-dependent transcription (Manganaro et al, 2014). …”
Section: Resultsmentioning
confidence: 91%
“…Results from this analysis led to the identification of 139 host factors that, when depleted, enhanced viral infection by 50% or more compared to the negative control with at least two independent siRNAs (Figure 1B; see Table S1 available online). Proteins involved in cell cycle regulation, ubiquitination, apoptosis, and DNA replication were found to be enriched in the set of 139 genes (Figure 1C), including CYLD, a gene we recently reported to regulate LTR-dependent transcription (Manganaro et al, 2014). …”
Section: Resultsmentioning
confidence: 91%
“…CYLD is best known as a major negative regulator of this pathway. There are several excellent reviews that detail the involvement of CYLD with NF-kB activation, including an extensive review by Chen on NF-kB and IKK [46, 72, 73]. After initial details of the negative regulation of NF-kB by CYLD emerged, it was found that TRAF3, TRAF5 and TRAF6 do not interact with CYLD but a TRAF-interacting protein (TRIP) does [7, 12].…”
Section: Cyld Functionmentioning
confidence: 99%
“…Expression was normalized by Ribosomal Protein S11 ( RPS11 ) expression using primers: Rps11 Fw GCCGAGACTATCTGCACTAC and Rps11 Rv ATGTCCAGCC TCAGAACTTC [36]. qPCR conditions were: 95°C for 10 min, followed by 40 cycles of 95°C for 10 s and 60°C for 60 s. Expression levels for individual RNAs were calculated based on their threshold cycle ( C T ) (ΔΔ C T values).…”
Section: Methodsmentioning
confidence: 99%